Mobius transform for Cadiag-2 - Harek, Petr; Phương, Nguyễn Hoàng (Journal of Computer Science and Cybernetics, 2016)
This study presents how the Mobius transform can be used for Max-Min compositions of rules of the CADIAG-2. The algorithm for Mobius transform to find new weights of rules for CADIAG-2 is proposed. This method is tested for different examples and some remarks are indicated.